Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevb.93.195206
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiophonon dispersion in crystalline naphthalene using van der Waals density functionals

Abstract: Acene molecular crystals are of current interest in organic optoelectronics, both as active materials and for exploring and understanding new phenomena. Phonon scattering can be an important facilitator and dissipation mechanism in charge separation and carrier transport processes. Here, we carry out density functional theory (DFT) calculations of the structure and the full phonon dispersion of crystalline naphthalene, a well-characterized acene crystal for which detailed neutron diffraction measurements, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 85 publications
6
71
0
Order By: Relevance
“…The GW correction is important as it stretches the valence band, thus lowering the hole effective mass and changing the relative alignment of the valence band valleys. The quality of our phonon dispersions is comparable with that of recent accurate phonon calculations in naphthalene [52]. To further validate our phonon calculations, we also compute the phonon dispersions of perdeuterated naphthalene, for which experimental data are available (see Fig.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…The GW correction is important as it stretches the valence band, thus lowering the hole effective mass and changing the relative alignment of the valence band valleys. The quality of our phonon dispersions is comparable with that of recent accurate phonon calculations in naphthalene [52]. To further validate our phonon calculations, we also compute the phonon dispersions of perdeuterated naphthalene, for which experimental data are available (see Fig.…”
Section: Methodssupporting
confidence: 72%
“…Calculated dispersion of the 12 intermolecular phonon modes for perdeuterated naphthalene, with lattice constants taken from Refs. [64], [52]. The markers are the experimental data at 6 K from Ref.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This is done by comparing the simulated DFT phonon band structure of deuterated naphthalene to the available experimental data 18 . As part of this comparison, different a posteriori van-der-Waals (vdW) corrections within DFT are tested, extending a previous study by Brown-Altvater et al 30 . DFTB-and FF-calculated phonon bands are, subsequently, compared to the results of the aforementioned DFT reference results.…”
Section: Introductionmentioning
confidence: 95%
“…Recent works have reported advances in the treatment of vdW interactions. Brown-Altvater, Rangel, and Neaton [38] showed that including vdW interactions enabled the accurate prediction of structural parameters and phonon frequencies of crystalline naphthalene. Kleis et al [39] accurately predicted structural, cohesive, and elastic properties for crystalline polyethylene by including vdW interactions via the vdW density functional [35].…”
mentioning
confidence: 99%